Students’ beliefs about portfolio evaluation and its influence on their learning outcomes to develop EFL in a Spanish context - Martínez-Lirola, María; Rubio, Fernando (International Journal of English Studies, 2009)
There is a significant world-wide apprehension concerning perceived deficiencies in university students’ performance and a resulting decrease of knowledge level and competency development. This paper analyses the benefits of using a portfolio as a means of evaluating student progress and the beliefs from which students draw their learning and motivation, a key issue for the incorporation of former curricular elements into the European Space for Higher Education consolidation process. Two studies conducted at two universities in Spain to explore students’ opinions of portfolio use surprisingly revealed that students found effort and daily work as the main beneficial aspects for their learning and motivation. Successful replication of this study in diverse contexts would imply that portfolio implementation can be a powerful instrument to empower students’ motivation to learn. Other results related to portfolio use will also be discussed.